Towards a Diagnosis of Cochlear Neuropathy with Envelope Following Responses - Shaheen, Luke A. (J Assoc Res Otolaryngol, 2015)
Listeners with normal audiometric thresholds can still have suprathreshold deficits, for example, in the ability to discriminate sounds in complex acoustic scenes. One likely source of these deficits is cochlear neuropathy, a loss of auditory nerve (AN) fibers without hair cell damage, which can occur due to both aging and moderate acoustic overexposure. Since neuropathy can affect up to 50 % of AN fibers, its impact on suprathreshold hearing is likely profound, but progress is hindered by lack of a robust non-invasive test of neuropathy in humans. Reduction of suprathreshold auditory brainstem responses (ABRs) can be used to quantify neuropathy in inbred mice. However, ABR amplitudes are highly variable in humans, and thus more challenging to use. Since noise-induced neuropathy is selective for AN fibers with high thresholds, and because phase locking to temporal envelopes is particularly strong in these fibers, the envelope following response (EFR) might be a more robust measure. We compared EFRs to sinusoidally amplitude-modulated tones and ABRs to tone-pips in mice following a neuropathic noise exposure. EFR amplitude, EFR phase-locking value, and ABR amplitude were all reduced in noise-exposed mice. However, the changes in EFRs were more robust: the variance was smaller, thus inter-group differences were clearer. Optimum detection of neuropathy was achieved with high modulation frequencies and moderate levels. Analysis of group delays was used to confirm that the AN population was dominating the responses at these high modulation frequencies. Application of these principles in clinical testing can improve the differential diagnosis of sensorineural hearing loss.